Aspects of the contribution of Church of Greece and Orthodox Theology in the development of bioethical dialogue - Χανιώτης (Evangelos Chaniotis) Ευάγγελος (Bioethica, 2016)
The importance of modern biomedical achievements along with the consequent ethical dilemmas, concerning the integrity of human person, incited the Church of Greece to establish a Special Synodical Committee of Bioethics. It was created in order to inform the people of Church responsibly and scientifically regarding all these bioethical issues. Those, however, were already known to Orthodox Theology even since the 1950s, when orthodox theologians, based on patristic theology, became involved in the bioethical dialogue when the issue of assisted reproduction was central. Afterwards, the Bishop of Demetrias Christodoulos (later, the Archbishop of Athens) deal with a wide range of bioethical issues in the light of Orthodox Theology. The Commission has dealt extensively with major ethical issues, such as the moment of death, the mechanical support in ER, the interfering with the normal process of reproduction, the beginning of the human life, the problem of euthanasia, the challenge of man’s intervention in the human genome, creating designer babies, the research and the experimentation on humans, especially on the fetus, the dependence of health on monetary profit, the use of medical technology on humans, thus contributing to the Orthodox Christian Ethics, and the total scientific dialogue. The Church assesses the bioethical issues above, and, through its theological tradition and life, formulates its pastoral advice and guidance hence focusing on vital issues such as the ethical limits in biomedical applications and the criteria that can set them. The Orthodox Bioethics is called to give answers to dilemmas which the biomedical sciences fail to do so or even lead to a deadlock.